Toluene degradation in a two-phase partitioning bioreactor involving a hydrophobic ionic liquid as a non-aqueous phase liquid. (February 2017) - Nguyen, Thi-vi-na; Rodriguez Castillo, Alfredo Santiago; Guihéneuf, Solène; Biard, Pierre-François; Paquin, Ludovic; Amrane, Abdeltif; Couvert, Annabelle
Abstract: An ionic liquid (IL), 1-octylisoquinolinium bis(trifluoromethyl-sulfonyl) imide also known as [OctIq][NTf2 ], was selected, since it complies with all the requested characteristics to be used as non-aqueous phase liquid (NAPL) in a two-phase partitioning bioreactor (TPPB) dedicated to the biological treatment of the hydrophobic volatile organic compound, toluene. Various operating parameters were investigated and the performances were compared to those recorded in the absence of NAPL. With an aeration flow rate of 0.2 L min −1 and in the presence of [OctIq][NTf2 ] as NAPL in a TPPB of 12 L, the system allowed to avoid toluene stripping and to totally remove toluene at different concentrations ranging from 0.55 to 1.13 g L −1 . However, and even if the ionic liquid addition seemed to decrease the toluene biodegradation rate, higher toluene concentrations could be treated due to the high affinity of toluene for the selected IL. For high toluene concentrations, biodegradation rate might be limited by the oxygen supply because the dissolved oxygen concentration was almost zero. [OctIq][NTf2 ] appears to be a suitable NAPL for the biological treatment of toluene. To improve both toluene and oxygen availabilities, the NAPL-to-water ratio should be investigated in order to optimize the interfacial area due to the dispersion of [OctIq][NTf2 ] droplets in water, as well as the effect of aeration rate on toluene biodegradation rates. Highlights: [OctIq][NTf2 ] complies with all the requested characteristics to be selected as non-aqueous phase liquid (NAPL). Several operating parameters were investigated in a TPPB of 12 L. Performances were compared to those recorded in the absence of NAPL. Ionic liquid allowed to avoid toluene stripping and increased the amount of toluene treated.